EFFICACY, SAFETY AND TOLERABILITY OF LAMOTRIGINE IN THE TREATMENT OF EPILEPSY - O. A. Pylaeva; K. Yu. Mukhin; M. B. Mironov (Русский журнал детской неврологии)
A review is devoted to the aspects of efficacy, safety and tolerability of lamotrigine in the treatment of epilepsy. Special emphasis is placed on the results of comparative studies, on such aspects of the treatment as the impact of the drug on cognitivefunction and quality of life. Especially the benefits of lamotrigine in children and adolescents are discussed in detail. Also indicationsfor using lamotrigine according to the international standards for treatment of epilepsy are considered.